BATAM FREE TRADE ZONE AND FREE PORT: A JURIDICAL REVIEW FROM THE ASPECT OF THE MOVEMENT OF IMPORTED GOODS - Ozy Diva Ersya (PETITA: JURNAL KAJIAN ILMU HUKUM DAN SYARIAH, 2020)
There are two prominent views concerning the free zone concept. One view defines a free zone as a special area established in a country that is independent from the customs authority supervision on the movement of imported goods, or known as extraterritorial zone, because customs authority is no longer levied import duties on these goods. On the other hand, the free zone is also defined as a special zone under the supervision of the customs authority due to the exemption of the import duties and tax on these imported goods as customs authority must ensure the validity of this exemption. In addition, there are also international instruments providing guidance concerning free zone, namely the WCO International Convention on the Simplification and Harmonization of Customs Procedures (the Revised Kyoto Convention) or the WCO RKC, and the WTO Agreement. This paper will discuss issues concerning the juridical aspects of the free zone concepts internationally and the practices in other countries in comparison to the applicable legal rules and practices related to the movement of imported goods in the Batam Free Trade Zone and Free Port (KPBPB Batam) and the surrounding islands. Abstrak: Terdapat dua pandangan terkait konsep free zone. Satu pandangan mendefinisikan free zone adalah sebagai suatu kawasan khusus yang didirikan disuatu negara dimana daerah tersebut terlepas dari wilayah otoritas Bea dan Cukai atau‘exterritorial’ area karena tidak ada lagi pengenaan pajak impor oleh otoritas Bea dan Cukai atas impor barang tersebut. Namun dilain pihak, free zone juga didefinisikan sebagai kawasan bebas yang khusus dibawah pengawasan otoritas Bea dan Cukai karena adanya perlakuan pembebasan bea masuk dan pajak tersebu dan otoritas Bea dan Cukai harus memastikan kebenaran pemberian pembebasan pajak impor tersebut. Selain itu, terdapat juga instrumen internasional yang setidaknya memberikan paduan terkait konsep kawasan bebas yaitu Konvensi WCO terkait dengan Simplifikasi dan Harmonisasi Prosedur Kepabeanan (Konvensi Kyoto) dan Perjanjian Internasional WTO. Paper ini akan membahas terkait dengan permasalahan yuridis dari aspek konsep free zone secara internasional dan praktek di negara lain dibandingkan dengan aturan hukum yang berlaku dan praktek pelaksanaannya dalam lalulintas barang di KPBPB Batam dan gugusan pulau sekitarnya. Kata Kunci: Kawasan Bebas, Kawasan Perdagangan Bebas, Perdagangan Internasional, Otoritas Kepabeanan, KPBPB Batam, Barang Impor